The art of strategic planning for information technology crafting strategy for the 90s - Boar, Bernard H. 1947- (John Wiley & Sons, Inc., 1993)
Computer Science/Information Technology The Art of Strategic Planning for Information Technology Drawing on the teachings of Sun Tzu and Machiavelli, this book offers a complete and integrated methodology for performing strategic business planning for information technology using the most modern techniques. It provides a complete analysis of the major trends impacting the information technology organization in the 1990s including business reengineering, client/server computing, downsizing, open systems, and the decline of IBM. The Art of Strategic Business Planning for Information Technology focuses on the topics of strategy and information technology-making strategy relevant, accessible, and understandable to the information technology professional.